PENINGKATAN KEMAMPUAN OPERASI PENGURANGAN DENGAN TEKNIK MEMINJAM MELALUI INQUIRY TRAINING BAGI ANAK BERKESULITAN BELAJAR KELAS IV DI SD NEGERI 02 GUNUNG SARIK PADANG - Ningrum Angjang Sana (Jurnal Penelitian Pendidikan Khusus, 2015)
ABSTRACTNingrum Angjang Sana. 2015. "Improved Operating Capabilities Through Borrowing Reduction Technique Training for Children Inquiry learning disabilities"(Single Subject Research at SDN 02 Gunung Padang Sarik Class IV). Essay. Department of Special Education.This study was motivated by the problems that the researchers found, a child learning disabilities experience obstacles IV class X in mathematics. Based on the assessment results known to the child have problems in arithmetic operations especially with the reduction in borrowing techniques. Based on this background of researchers working to help improve children's ability in arithmetic operations through the reduction of Inquiry Training.This study aims to improve the ability of arithmetic operation subtraction with borrowing through the Inquiry Training techniques children learn berkesulitan Sarik SDN 02 Gunung Padang. The research is a Single Subject Research (SSR). This research uses design A-B-A.From the research shows that the arithmetic operation capability reduction berkesulitan children learn in grade IV SDN 02 Gunung Padang Sarik, increased after the intervention using a given model of Inquiry Training. At baseline conditions were carried out for six sessions, no success is achieved the frequency of children. On the condition of intervention using Training Inquiry, conducted over eight times the frequency of meeting the child's success in answering the question reached ninety. Whereas in the baseline condition (A2) after the intervention is no longer granted performed during five meetings, the child is able to maintain the operating capability of reduction to obtain a frequency count reaches ninety success. Thus the formulation of the problem raised Inquiry Training missed that effectively increase the operating capability reduction with techniques borrowed for children fourth grade learning disabilities Sarik SDN 02 Gunung Padang.